Compressive behaviour of old one-leaf stone masonry walls; the influence of patterns' regularity and constructive process - Celeste Almeida (2021)
This paper studies the influence of the constructive process and the regularity pattern on the behaviour of oneleaf stone masonry walls in compression through an experimental campaign. The walls under study correspond to the main load bearing elements of most of the old buildings of the historic centre of Porto, Portugal, but also of many others located at the Northern part of the territory. For this purpose, twenty-four specimens were constructed with distinct textures, corresponding to different regularity patterns in agreement to the walls geometrical and material characteristics assessed through in-situ campaigns, and following the observed in-situ constructive procedures. Twelve of these specimens were tested under uniaxial compression, which allowed quantifying the mechanical characteristics of the masonry, namely the strength and deformability. In particular, the tests also permitted relating the results with the regularity patterns, showing that a similar behaviour is obtained for most of the textures and that the constructive process plays a major role on the specimens' final behaviour, namely on the low stiffness-to-strength ratios with values well below those currently provided in standards or suggested in the literature.